Analisis Kepuasan Pasien Dilihat dari Minat untuk Dirawat Kembali Terhadap Pelayanan Dokter dan Perawat - Lailil Masruron; Tjahjono Kuntjoro; Martha Irene Kartasurya (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2019)
Title :Patient Satisfaction To Doctor’s And Nurse’s Care Associated To The Interest To Be Rehospitalized (A study at RSUD Dolopo, Madiun Regency). AbstractBed Occupancy Rate (BOR) at Dolopo Public Hospital had decreased from 56.16% in 2013 to 35.86% in 2104 and 35.2% in 2015, and the average ALOS (Average Length of Stay) and Turn over Interval (TOI) increased. The preliminary study on patients of Social Security Agency (BPJS Non PBI) showed a dissatisfaction to nurse’s and doctor’s services. The aim of this study was to analyze the associations between patient satisfaction toward doctor’s & nurse’s services to the interest to be rehospitalized.This study was conducted in a cross sectional design. The subjects were 95 patients of BPJS with Non PBI in inpatient room for class I, II, III, which was choosen by using accidental sampling. Data were gathered through interviews using structured questionnaires. Data analysis was conducted by Chi-square tests and logistic regression.Results showed that the patient satisfaction based on aspects of tangibles, reliability, responsiveness, assurance, and empathy were lower than the expectations. Most of the subjects have positive attitudes, negative subjective norms and perceptions of behavior control and had a poor accesibility to the hospital. However 75.8% of the respondents were interested to be rehospitalized at Dolopo Hospital. There were correlations between patient satisfaction (p=0.009), attitude (p=0.000), subjective norm (p=0.002) with the interest to be rehospitalized. There was no correlation between control perception behavior (p=0.103), and access (p = 0.454) with the interest to be rehospitalized. After controlled for the attitude toward doctors’ and nurses’ services, the patients who were satisfied to the doctor’ and nurses’ services had 3.84 times to be interested to be rehospitalized than the patients who were not satifsfied (OR = 3.84 ; CI 95% : 0.98-15.12, p=0.054).Keywords : Patient Satisfaction, Rehospitalized, BPJS.